Chemical Synthesis of K34‐Ubiquitylated H2B for Nucleosome Reconstitution and Single‐Particle Cryo‐Electron Microscopy Structural Analysis. (15th December 2016) - Li, Jiabin; He, Qiaoqiao; Liu, Yuntao; Liu, Sanling; Tang, Shan; Li, Chengmin; Sun, Demeng; Li, Xiaorun; Zhou, Min; Zhu, Ping; Bi, Guoqiang; Zhou, Zhenghong; et al.
Abstract: Post‐translational modifications (e.g., ubiquitylation) of histones play important roles in dynamic regulation of chromatin. Histone ubiquitylation has been speculated to directly influence the structure and dynamics of nucleosomes. However, structural information for ubiquitylated nucleosomes is still lacking. Here we report an alternative strategy for total chemical synthesis of homogenous histone H2B‐K34‐ubiquitylation (H2B‐K34Ub) by using acid‐cleavable auxiliary‐mediated ligation of peptide hydrazides for site‐specific ubiquitylation. Synthetic H2B‐K34Ub was efficiently incorporated into nucleosomes and further used for single‐particle cryo‐electron microscopy (cryo‐EM) imaging. The cryo‐EM structure of the nucleosome containing H2B‐K34Ub suggests that two flexible ubiquitin domains protrude between the DNA chains of the nucleosomes. The DNA chains around the H2B‐K34 sites shift and provide more space for ubiquitin to protrude. These analyses indicated local and slight structural influences on the nucleosome with ubiquitylation at the H2B‐K34 site. Abstract : Ubiquitous ubiquitylation : A ubiquitylated histone (H2B‐K34Ub) was synthesized by ligating peptide hydrazides with an acid‐cleavable auxiliary. Single‐particle cryo‐EM analysis of nucleosomes containing H2B‐K34Ub indicated two highly flexible ubiquitin domains protruding between DNA chains wrapping the nucleosome that could result in conformational and slight structural changes in the nucleosome.